2012
DOI: 10.1029/2012gl052749
|View full text |Cite
|
Sign up to set email alerts
|

Sea surface temperature variability in southern Okinawa Trough during last 2700 years

Abstract: Most of the temperature reconstructions for the past two millennia are based on proxy data from various sites on land. Here we present a bidecadal resolution record of sea surface temperature (SST) in Southern Okinawa Trough for the past ca. 2700 years by analyzing tetraether lipids of planktonic archaea in the ODP Hole 1202B, a site under the strong influence of Kuroshio Current and East Asian monsoon. The reconstructed SST anomalies generally coincided with previously reported late Holocene climate events, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 50 publications
3
36
0
Order By: Relevance
“…Our finding of warmer SSTs in the 20th/21st centuries and MCA period and cooler SSTs during the LIA is broadly consistent with other records from the western Pacific region. For example, SST during the MCA in the Southern Okinawa Trough (East China Sea) was 25.7°C, 0.4°C lower than that in the 20th century (Wu et al, ). Similarly, planktonic foraminiferal Mg/Ca‐SST records from the Makassar Strait (Indonesia) showed warm temperatures and high salinities occurred during the MCA, while the SSTs during the LIA were ~1.5°C cooler than present (Newton et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of warmer SSTs in the 20th/21st centuries and MCA period and cooler SSTs during the LIA is broadly consistent with other records from the western Pacific region. For example, SST during the MCA in the Southern Okinawa Trough (East China Sea) was 25.7°C, 0.4°C lower than that in the 20th century (Wu et al, ). Similarly, planktonic foraminiferal Mg/Ca‐SST records from the Makassar Strait (Indonesia) showed warm temperatures and high salinities occurred during the MCA, while the SSTs during the LIA were ~1.5°C cooler than present (Newton et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the present-day climate conditions and the potential trends of future climate change, it is necessary to extend the temporal scale of investigation into the last millennium [Jones et al, 1998;McGregor et al, 2015]. The last millennium includes three distinct climate intervals: the Medieval Climate Anomaly (MCA, AD 900-1300) [Lamb, 1965;Crowley and Lowery, 2000], the Little Ice Age (LIA, AD 1550-1850 [Robock, 1979;Bradley and Jones, 1993], and the Current Warm Period (CWP, AD 1850-present) [Wu et al, 2012;Fleury et al, 2015]. The MCA and LIA are climate anomalies that were caused by natural forcing (e.g., solar variability and volcanic emissions), but the CWP is linked to anthropogenic factors (e.g., industrialization and land-use changes) [Masson-Delmotte et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, many studies have investigated SST in the OT using various proxies (e.g., Zhao et al, 2005;Ijiri et al, 2005;Zhou et al, 2007;Yu et al, 2009;Chen et al, 2010;Kubota et al, 2010;Wu et al, 2012). Records of SST based on U K' 37 from the southern OT revealed that warming during the last deglaciation was synchronous with ice volume changes, but lagged the warming in Greenland's ice core record and the terrestrial monsoon record (Zhao et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The southern OT is less sensitive to the influence of cold water than the northern OT and is more suitable for the use of multiple proxies for paleotemperature studies. So far, however, only a few reconstructions of SST exist in the southern OT (Zhao et al, 2005;Wu et al, 2012). This paper aims to use three temperature proxies (foraminiferal Mg/Ca, U K' 37 and ) to determine SST variations in the southern OT since the last deglaciation and to examine the response of regional SST to both Northern and Southern Hemisphere climate and local KC modulation.…”
Section: Introductionmentioning
confidence: 99%